Globalization and the making of religious modernity in China: transnational religions, local agents, and the study of religion, 1800-present - Jansen, Thomas; Klein, Thoralf; Meyer, Christian (Religion in Chinese societies, 2014)
Globalization and the Making of Religious Modernity in China investigates the transformation of China's religious landscape under the impact of global influences through case studies covering the period from 1800 to the present